Pitfall trapping outperforms other methods for surveying ground-dwelling large-bodied alpine invertebrates - Aaron Bertoia; Tara Murray; Bruce C. Robertson; Joanne M. Monks (Journal of Insect Conservation, 2023)
Appropriate sampling methods are essential for monitoring and managing all wildlife. There is limited information on how to monitor ground-dwelling invertebrates in the alpine zone compared to more commonly studied lower-elevation habitats. We aim to understand the strengths, weaknesses, and cost-effectiveness of invertebrate survey methods when deployed in the alpine zone. We tested four methods on the South Island of New Zealand (Aotearoa): pitfall traps, tracking tunnels, visual surveys, and trail cameras. We focused on methods for ground-dwelling large-bodied invertebrates, a group most likely to be impacted by introduced mammalian predators. Pitfall traps and trail cameras were practical methods for surveying alpine invertebrates. Tracking tunnels only reliably detected large wētā (Orthoptera: Anostostomatidae), as other invertebrates were too light to leave distinguishable tracks. Visual surveys did not generate enough observations to be considered a successful method. We found no difference in the total abundance or easily recognised taxonomic groups detected by pitfall traps and trail cameras. Trail cameras detected fewer wētā compared to tracking tunnels and pitfall traps. Of the successful methods, pitfall traps were the most cost-effective, followed by tracking tunnels and trail cameras. Tracking tunnels were the fastest to install and required the least processing time, followed by pitfall traps and trail cameras. We recommend using pitfall traps to survey large-bodied alpine ground-dwelling invertebrates to better understand population trends or community composition. This method was consistent across all alpine habitat types and has the potential to be an effective method to inform conservation monitoring and management programmes. Implications for insect conservation Monitoring is vital to understand how invertebrates respond to change and evaluate conservation management program outcomes. This study provides practical information on potential monitoring tools for invertebrates in the alpine zone and recommends pitfall traps to survey large-bodied alpine invertebrates.